2012
DOI: 10.1002/ange.201206596
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐Platinum/Thiazole Complex Interferes with Sp1 Zinc‐Finger Protein

Abstract: Keine Migration: Der antitumoraktive trans‐Platin‐Thiazol‐Komplex trans‐PtTz zeigt gegenüber dem Transkriptionsfaktor SP1, der in Tumorzellen überexprimiert ist, eine hohe Reaktivität. Die Anbindung von trans‐PtTz stört die Wechselwirkung der DNA mit Sp1 in vitro und verhindert die Migration des Proteins aus dem Cytoplasma in den Zellkern (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It has been found that cisplatin could react with some ZFPs resulting in the release of zinc ions from ZFPs and the perturbations of protein structures and functions , . However, some other ZFPs demonstrated a much lower reactivity to cisplatin . To further understand the influence of the zinc binding motif in the reaction with cisplatin, and also to exclude the possibility of varying results occurring from different investigation conditions, we conducted a reaction of three types of ZFPs under identical reaction conditions and analyzed the reactions using several methods, including NMR, HPLC, ESI‐MS, and CD spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that cisplatin could react with some ZFPs resulting in the release of zinc ions from ZFPs and the perturbations of protein structures and functions , . However, some other ZFPs demonstrated a much lower reactivity to cisplatin . To further understand the influence of the zinc binding motif in the reaction with cisplatin, and also to exclude the possibility of varying results occurring from different investigation conditions, we conducted a reaction of three types of ZFPs under identical reaction conditions and analyzed the reactions using several methods, including NMR, HPLC, ESI‐MS, and CD spectra.…”
Section: Resultsmentioning
confidence: 99%
“…While a number of ZFPs demonstrated high reactivity to cisplatin, the zinc finger protein Sp1 showed very low reactivity to cisplatin, although this reaction can be significantly promoted by tris‐(2‐carboxyethyl) phosphine (TCEP) through a cisplatin‐TCEP intermediate . On the other hand, a trans ‐platinum derivative [PtCl 2 (NH 3 )(thiazole)] possesses a much higher reactivity than cisplatin to Sp1.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the reaction with H1, the nonlabile ligands were found to be preserved in the reaction of trans-EE or trans-PtTz with the human copper chaperone Atox1 or the Zinc-Finger protein Sp1. 58,59 ■ CONCLUSIONS…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, serious side effects from Pt­(II) drugs have limited their clinical use. Recently, platinum­(IV) (Pt­(IV)) complexes were designed by introducing two additional ligands to the axial positions, which decompose to the corresponding toxic Pt­(II) drugs under photoirradiation or chemical reduction. Apart from being drugs, Pt could be used as a CT imaging contrast agent due to its high X-ray absorption coefficient . Compared to organic drug molecules, the use of Pt-based CT imaging could self-track the fate of Pt-based anticancer drugs in vivo .…”
mentioning
confidence: 99%